The Effects of COVID-19 Lockdown 1.0 on Working Patterns, Income, and Wellbeing Among Performing Arts Professionals in the United Kingdom (April–June 2020) - Spiro, Neta; Perkins, Rosie; Kaye, Sasha; Tymoszuk, Urszula; Mason-Bertrand, Adele; Cossette, Isabelle; Glasser, Solange; Williamon, Aaron (Frontiers in Psychology, 2021)
This article reports data collected from 385 performing arts professionals using the HEartS Professional Survey during the COVID-19 Lockdown 1.0 in the United Kingdom. Study 1 examined characteristics of performing arts professionals’ work and health, and investigated how these relate to standardized measures of wellbeing. Study 2 examined the effects of the lockdown on work and wellbeing in the respondents’ own words. Findings from Study 1 indicate a substantial reduction in work and income. 53% reported financial hardship, 85% reported increased anxiety, and 63% reported being lonelier than before the crisis. 61% sought support on finances while only 45% did so on health and wellbeing. Multiple regression analyses, using the Mental Health Continuum-Short Form, Center for Epidemiologic Studies Depression Scale, Social Connectedness Scale, and Three-Item Loneliness Scale as outcome variables, indicate that perceived financial hardship was associated with lower wellbeing and higher depression and loneliness scores. Higher self-rated health was associated with higher wellbeing and lower depression scores. More physical activity before lockdown was associated with higher wellbeing and social connectedness scores, as well as lower loneliness scores, and an increase in physical activity during lockdown compared with before, as well as older age, were associated with higher wellbeing and social connectedness scores, and lower depression and loneliness scores. Thematic inductive analysis of 341 open responses in Study 2 identified five overarching themes characterizing the effects of Lockdown 1.0: lost or uncertain work and income, including canceled work, financial concerns, and uncertainties for the future; constraints of lockdown working, including challenges of working at home, struggles with online work and skill maintenance, and caring responsibilities; loss and vulnerability, including reduced social connections, lack of support, vulnerability, feelings of loss and grief, and concern for others; detrimental effects on health and wellbeing, including anxiety, low or unstable mood, poorer physical health, and lack of motivation; and professional and personal opportunities, including coping well or living more healthily, more time and less pressure, new possibilities and activities, enhanced social connections, and new skills. Lockdown 1.0 had profound effects on performing arts professionals, but our findings reveal some opportunities and compelling links between positive wellbeing and physical activity.